The vision machine - Virilio, Paul (Bloomington, Ind. : Indiana University Press ; London : British Film Institute, 1994)
Surveying art history as well as the technologies of war and urban planning, one of France's leading intellectuals provides an introduction to a new "logistics of the image."
Prijevod djela: La machine de vision
Bibliografske bilješke uz poglavlja
Kazalo
Keywords: Art -- Psychology; Art and technology; Visual communication; Visual perception; umjetnost; psihologija; umjetnost i tehnologija; vizualna komunikacija; vizualna precepcija